Association Between DRD2 and DRD4 Polymorphisms and Eating Disorders in an Italian Population - Ceccarini, Maria Rachele; Fittipaldi, Simona; Ciccacci, Cinzia; Granese, Erika; Centofanti, Federica; Dalla Ragione, Laura; Bertelli, Matteo; Beccari, Tommaso; Botta, Annalisa (Frontiers in Nutrition, 2022)
Anorexia Nervosa (AN), Bulimia Nervosa (BN), and Binge Eating Disorder (BED) are the three most common eating disorders (EDs). Their etio-pathogenesis is multifactorial where both environmental and genetic factors contribute to the disease outcome and severity. Several polymorphisms in genes involved in the dopaminergic pathways seem to be relevant in the susceptibility to EDs, but their role has not been fully elucidated jet. In this study we have analysed the association between selected common polymorphisms in the DRD2 and DRD4 genes in a large cohort of Italian patients affected by AN (n= 332), BN (n= 122) and BED (n= 132) compared to healthy controls (n= 172). Allelic and genotypic frequencies have been also correlated with the main psychopathological and clinical comorbidities often observed in patients. Our results showed significant associations of the DRD2-rs6277 SNP with AN and BN, of the DRD4-rs936461 SNP with BN and BED and of DRD4 120-bp TR polymorphism (SS plus LS genotypes) with BED susceptibility. Moreover, genotyping of DRD4 48-bp VNTR identified the presence of ≥7R alleles as risk factors to develop each type of EDs. The study also showed that ED subjects with a history of drugs abuse were characterized by a significantly higher frequency of the DRD4 rs1800955 TT genotype and DRD4 120-bp TR short-allele. Our findings suggest that specific combinations of variants in the DRD2 and DRD4 genes are predisposing factors not only for EDs but also for some psychopathological features often coupled specifically to AN, BN and BED. Further functional researches are needed to better clarify the complex role of these proteins and to develop novel therapeutic compounds able to modulate dopamine neurotransmission.